2019
DOI: 10.4067/s0718-10432019005000502
|View full text |Cite
|
Sign up to set email alerts
|

Cambios políticos, sociales y económicos en relación a la pesca y extracción del guano en la costa de Arica y Tarapacá: siglos XVI a inicios del XIX

Abstract: El litoral del desierto de Atacama ha sido una fuente de obtención de energía importante y un medio para la vida social de las poblaciones prehispánicas y coloniales. Peces, mariscos y mamíferos marinos fueron productos claves en la dieta humana, a lo que se sumó el guano en los intercambios económicos y simbólicos y en el desarrollo agrícola. Tales actividades depredadoras y de recolección impulsaron la utilización de tecnologías e instrumentos para su acceso y tráfico, que reflejan procesos sociales de compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
2
Order By: Relevance
“…Experimental research has demonstrated that fertilization using bird guano and camelid dung can significantly increase nitrogen isotopic values in plant tissues (Szpak et al, 2012). Fertilizing crops with marine bird guano is a well-documented practice in many Andean coastal valleys during late Pre-Columbian and Colonial times (Hidalgo et al, 2019) and significantly high δ 15 N values have been reported in human, camelids, maize, macaws, and other animal and plant remains in sites such as Azapa 8, Camarones 8, Pica 8, and many more spread out throughout the Atacama Desert (King et al, 2018;Alfonso-Durruty et al, 2019;Capriles et al, 2021;Santana-Sagredo et al, 2021). Therefore, our isotopic results seem to verify the hypothesis that food crops were not only cultivated locally but also fertilized using bird guano (Szpak, 2014;Santana-Sagredo et al, 2021).…”
Section: Niche Construction and The Domestication Of The Desertmentioning
confidence: 99%
“…Experimental research has demonstrated that fertilization using bird guano and camelid dung can significantly increase nitrogen isotopic values in plant tissues (Szpak et al, 2012). Fertilizing crops with marine bird guano is a well-documented practice in many Andean coastal valleys during late Pre-Columbian and Colonial times (Hidalgo et al, 2019) and significantly high δ 15 N values have been reported in human, camelids, maize, macaws, and other animal and plant remains in sites such as Azapa 8, Camarones 8, Pica 8, and many more spread out throughout the Atacama Desert (King et al, 2018;Alfonso-Durruty et al, 2019;Capriles et al, 2021;Santana-Sagredo et al, 2021). Therefore, our isotopic results seem to verify the hypothesis that food crops were not only cultivated locally but also fertilized using bird guano (Szpak, 2014;Santana-Sagredo et al, 2021).…”
Section: Niche Construction and The Domestication Of The Desertmentioning
confidence: 99%
“…Por otra parte, la hipótesis de Francisco Rothhammer y colaboradores (2010), sostienen que los pueblos de pescadores de las costas de Arica del siglo XVI, poseían una larga tradición cultural que se remontaba a milenios antes de la era cristiana, recibiendo a lo largo del tiempo distintas denominaciones, tales como Urus de la costa, Camanchacas, Proanches o Changos, que compartieron el espacio ecológico con colonias de Urus altiplánicos, quienes estaban en calidad de colonos de los señores del Collao y Charcas. La cohabitación de pescadores locales y altiplánicos en Arica, también es sugerida en diversos documentos estudiados por Bente Bittmann (1984), Jorge Hidalgo (1987Hidalgo ( , 2009Hidalgo ( y 2019 y María Rostworowski (1986, 2004 y 2005), por tanto, ¿Cuáles son las diferencias culturales y sociales entre los pescadores Urus altiplánicos y Camanchacas? Rómulo Cúneo-Vidal, realizó una temprana vinculación hipotética entre Camanchacas y Urus, siendo los primeros una ramificación de los pescadores altiplánicos (Cúneo-Vidal 1977b).…”
Section: Una Vieja Discusión Los Pescadores En Las Costas De Arica: U...unclassified
“…Sin embargo, dicha visión es errónea según las indagaciones arqueológicas de Adán Umire y Ana Miranda (2001) y los estudios etnohistóricos de Helena Horta (2010). En contraste, diversos estudios han señalado que, tanto Urus como pescadores yungas, formaron sus propias parcialidades, jefaturas étnicas y estaban organizados jerárquicamente en territorios delimitados para fines rituales y productivos (Choque y Pizarro 2012;Espinoza 2015;Hidalgo 1981Hidalgo , 1983Hidalgo , 2004Hidalgo , 2009Hidalgo y Focacci 1986;Hidalgo et al, 2019;Horta 2010Horta , 2015Muñoz y Choque 2013;Murra 1972;Rostworowski 1986Rostworowski , 2004Rostworowski y 2005.…”
Section: Los Camanchacas Gentes De La Mar Y La Tierraunclassified
“…Pastoralists employed a range of risk-sharing techniques, such as seasonal shifting, enhancing wild food productivity, dispersing herds over large areas to take advantage of local patch types, multispecies diversification, or increasing herd size (Browman, 1974(Browman, , 1987cDillehay, 2013). Water management and the use of manure of both marine and terrestrial origins were key to expanding the patchy green areas (Hidalgo, 2009;Hidalgo et al, 2019;Santana-Sagredo et al, 2021;Santoro et al, 1998), and agroforestry or silvopastoralism could provide a fertile cycle of nutrients to support desert life within a highly dynamic socioecological context.…”
Section: Introductionmentioning
confidence: 99%